A KALA SWETA: REFLEKSI KRITIS ALIH FUNGSI LAHAN DI BALI DALAM GARAPAN WAYANG WAHYA LAKU: KALA SWETA: REFLEKSI KRITIS ALIH FUNGSI LAHAN DI BALI DALAM GARAPAN WAYANG WAHYA LAKU - I Ketut Esa Indranata; I Ketut Kodi; I Ketut Sudiana (JURNAL DAMAR PEDALANGAN, 2026)
The accelerating conversion of agricultural land in Bali has reached a critical stage, threatening the sustainability of the Subak system as a cultural and ecological foundation of Balinese life. Responding to this phenomenon, the Wayang Wahya Laku performance Kala Sweta was created as an artistic medium of ecological reflection and social criticism toward the degradation of agrarian values and environmental balance. This study aims to examine the creative process, aesthetic construction, and philosophical dimensions of Kala Sweta, which integrates the mythological narrative of I Gudug Basu with contemporary socio-ecological realities in Bali. Employing a qualitative descriptive method through an art creation approach based on the creative stages of Alma M. Hawkins, the study involved participatory observation in Subak Lanyahan, in-depth interviews, and document analysis. This research offers an aesthetic interpretation of puppetry as a medium of ecological criticism through the integration of puppet symbolism, corporeal theatricality, and environmental narratives grounded in Balinese local wisdom. The findings reveal that Kala Sweta successfully transforms elements of Wayang Lemah and theatrical puppetry into a communicative artistic form that reinforces environmental awareness through visual symbolism, dramaturgical innovation, and the philosophical values of Tri Hita Karana.